Agronomic characters and quality of fruit of Salak cv. Gulapasir planted in various agro-ecosystems - Sumantra, I Ketut; Widnyana, I Ketut; Eka Martingsih, Ni Gusti Agung; Tamba, I Made; Adinurani, Praptiningsih Gamawati; Ekawati, Ida; Mel, Maizirwan; Soni, Peeyush (Hashemite University, 2023)
Salak [Salacca zalacca (Gaertn.) Voss] var. amboinensis cv. Gulapasir has been officially released by the Minister of Agriculture of the Republic of Indonesia since 1994. Salak ‘Gulapasir ’is one of five types of fruit that have been designated as the superior fruit of the Bali Province. Salak ‘Gulapasir’ is preferred by consumers due to its specific fruit flesh taste. Salak ‘Gulapasir’ was propagated using seeds so that a new type of salak emerged. However, the characters of this new type of salak ‘Gulapasir’ are not yet known. The research objective was to obtain the superior products of Salak ‘Gulapasir’ both in quantity and quality. The research used a Randomized Block Design with three replications. The non-independent variable was the three of Salak ‘Gulapasir’ (SGP): SGP var. nangka (N), SGP var. nenas (NS), SGP var. gondok (G), and six sites, namely Karangasem: (K < 560 m asl, K 560 m to 650 m asl, and K > 650 m asl) and Tabanan: (T < 560 m asl, T 560 m to 650 m asl, T > 650 m asl). Observations were made on the agronomic characters and fruit quality. Data were analyzed using variance analysis, and if the planting location and varieties show a difference, then it is followed by the LSD test at the 5 % level. The results showed that different varieties caused different fruit weights, fruit bunches, TSS, and total acid ratio. In Karangasem and in Tabanan, SGP var. nangka grows ideally at an altitude of 560 m to 650 m asl with fruit weight per tree of 1.62 kg-1 and 1.29 kg-1, respectively. SGP var. nenas and SGP var. gondok are ideal for cultivating at an altitude of < 560 m asl both in Karangasem and Tabanan, but the fruit production of SGP var. nenas and SGP var. gondok is higher, respectively 19.29 % and 15.31 % when planted in Karangasem, while the SGP var. nenas showed the highest number of fruit bunches-1 in six locations. Further research can be applied using sustainable salak organic agriculture to maintain soil fertility.